A guide to designing and implementing local and wide area networks - 1948-; Sinclair, Robert Bruce (Cambridge, Mass. : Course Technology, 1999)
"A Guide to Designing and Implementing Local and Wide Area Networks offers a unique approach to learning about network design, by providing both the theories behind networks and a practical, hands-on method of putting those theories to work. With extensive end-of-chapter exercises, hands-on exercises, and case studies, this book prepares you to design a network from the ground up, using real-world situations."--BOOK JACKET.
Ch. 1. An Overview of Networking in a LAN/WAN Environment -- Ch. 2. LAN/WAN Interconnectivity -- Ch. 3. Physical Transmission Options -- Ch. 4. Transmission Equipment -- Ch. 5. LAN/WAN/LAN Connections -- Ch. 6. Integration of Voice and Data: Optimizing Your Bandwidth -- Ch. 7. TCP/IP Past, Present, and Future -- Ch. 8. WAN Transport Methods -- Ch. 9. ATM Technologies -- Ch. 10. Network Protocol Architectures: Advantages and Disadvantages -- Ch. 11. Future Technologies and Services.
Keywords: Local area networks (Computer networks); Wide area networks (Computer networks)